Probing turbulence in solar flares from SDO/AIA emission lines - Xie, Xiaoyan; Li, Gang; Reeves, Katharine K.; Gou, Tingyu (Frontiers in Astronomy and Space Sciences, 2024)
Multiple pieces of evidence have revealed the important role of turbulence in physical processes in solar eruptions, from particle acceleration to the suppression of conductive cooling. Radio observations of density variation have established a Kolmogorov-like spectrum for solar wind density disturbance. Close to the Sun, measurements from extreme ultraviolet (EUV) bands have been used to examine turbulence in the solar atmosphere. The Atmospheric Imaging Assembly onboard the Solar Dynamics Observatory (SDO/AIA) has been frequently used for diagnosing plasma properties due to its complex coverage of temperature response. We compute structure functions (SFs) using SDO/AIA emission measurements for two example of plasma sheets. With the relationship of v ∼ b ∼ δn and δI∼δ(n0+δn)2∼δn (v, b, δn, and δI are turbulent velocity, magnetic field, number density, and intensity, respectively, and n0 is the background density), SFs of δI can be regarded as a proxy for those of the turbulent v and b fields in the plasma sheet. We show that by properly accounting for the radial dependence of the emission line intensity, an SF method is capable of probing the presence of turbulence from SDO/AIA emission lines. Compared to in situ observations, performing SFs on EUV emissions is advantageous in studying turbulence behavior in the wave-vector space, and it opens a new window for investigating turbulence from massive SDO/AIA observations.